Wireless quantum power distribution system based on wireless - Jiawei WU; Yuxiang BIAN; Qing ZHANG; Bao FENG (Dianxin kexue)
The traditional optical fiberchannel-based key distribution method is limited by the optical fiber resources and construction cost,and it is difficult to meet the security enhancement requirements of the access side massive power service terminals,especially the mobile terminals.In this respect,a wireless channel-based quantum key distribution system was proposed,which was suitable for mass service terminals of power systems.Based on the wireless access requirements of mass service terminals in power system,the overall design of power quantum key distribution system based on wireless channel was given.The functional modules and execution flow of the power quantum key distribution system based on wireless channel were analyzed in detail from three aspects:quantum security service control platform,quantum key storage management platform and massive power service terminal platform.On this basis,combined with the typical power service such as electricity information collection and mobile office,the advantages and prospects of the quantum channel distribution system based on wireless channel applied to the terminal scenario of massive power service were comprehensively analyzed.